The Effect of Storytelling on Receptive Language Development in Early Childhood: A Systematic Literature Review - Sukmakarti, Laksmy Dewi (Politeknik Kesehatan Kemenkes Surakarta, 2024)
Background: Early childhood education (PAUD) has an important role in developing children's language skills, both expressive and receptive language. One effective method for improving language development is through storytelling. Storytelling can stimulate children's cognitive and linguistic abilities by providing an in-depth social and emotional context. Objectives: This study aims to how storytelling can be used effectively to improve receptive language development in early childhood. Methods: This research uses a Systematic Literature Review. This research was carried out by collecting and selecting various data from previous studies as well as the results of clinical trials conducted between 2019 and 2024 from the Google Scholar data base. Results: Storytelling that involves two-way interaction and allows children to retell or discuss stories can improve their understanding of language structure and vocabulary. Conclusion: Applying storytelling to young children can improve receptive language skills. Keywords : Storytelling, Receptive language, Early childhood